2021
DOI: 10.1021/acs.biomac.1c00213
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Piezoelectric Properties of a Single-Peptide Nanotube Composed of Cyclic β-peptides with Helical Peptides on the Side Chains

Abstract: To develop nanopiezoelectronics, it is necessary to investigate the relationship between the sizes and piezoelectric properties of the material. Peptide nanotubes (PNTs) composed of cyclic β-peptides have been studied as leading candidates for nanopiezoelectric materials. The current drawback of PNTs is aggregation to form a PNT bundle structure due to strong dipole–dipole interactions between PNTs. Here, we report the construction and piezoelectric properties of single PNTs without nonspecific aggregation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The side chain introduced helical peptide has a three‐dimensional structure, which can hinder the contact between PNTs, resulting in the formation of a single PNT structure. The piezoelectric experiment results show that the converted piezoelectric response of a single PNT is 1.39±0.12 pm V −1 , which achieved strong piezoelectric performance through smaller‐sized nanostructures [116] . A recent study revealed a peptide‐based co‐assembly strategy that achieves a dramatic improvement in piezoelectric performance.…”
Section: Applications Of Peptide‐based Self‐assemblymentioning
confidence: 99%
“…The side chain introduced helical peptide has a three‐dimensional structure, which can hinder the contact between PNTs, resulting in the formation of a single PNT structure. The piezoelectric experiment results show that the converted piezoelectric response of a single PNT is 1.39±0.12 pm V −1 , which achieved strong piezoelectric performance through smaller‐sized nanostructures [116] . A recent study revealed a peptide‐based co‐assembly strategy that achieves a dramatic improvement in piezoelectric performance.…”
Section: Applications Of Peptide‐based Self‐assemblymentioning
confidence: 99%
“…The temperature impact on piezoelectric for biological applications was explored by Rotan et al (2021). For in vivo evaluation, biomaterials such as AIN-based flexible nanogenerator (Mariello et al, 2021), KNN-based lead-free heterogeneous structure PEH (Zhang et al, 2021a) and helical peptide nanotube-based NG (Kurita et al, 2021) are particularly suited and compatible.…”
Section: Reviewmentioning
confidence: 99%
“…α-Peptides comprising proteinogenic amino acids usually suffer from poor pharmacological properties, such as low metabolic stability and cell membrane permeability. Specialty peptides, including N-methylated peptides, , β-peptides, , and cyclic peptides, , generally have higher metabolic stability. In particular, it is believed that cyclic N-methylated peptides have better affinity and specificity against their biological targets because of their constrained chemical structure.…”
Section: Microflow Syntheses Of Specialty Peptides Including N-methyl...mentioning
confidence: 99%